Fairness in Olympic sports: How can we control the increasing complexity of doping use in high performance sports? - Herzog, W. (Journal of Sport and Health Science, 2017)
With the Rio Olympics just a few months past, we remember the excitement, the incredible performances, and the controversies. As happens so often, the Olympic Games focus attention not only on athletic achievements but also on how athletes may reach ever-increasing levels of performance. Doping, medical doping exemptions, and the ban of the Russian team for state-sponsored organized doping of its athletes dominated the discussions.